2016
DOI: 10.1111/aos.13247
|View full text |Cite
|
Sign up to set email alerts
|

Reduced metabolic function and structural alterations in inherited retinal dystrophies: investigating the effect of peripapillary vessel oxygen saturation and vascular diameter on the retinal nerve fibre layer thickness

Abstract: It becomes evident from our combined metabolic-structural approach that a prediction model, to identify which individual is at risk of developing a photoreceptor degeneration of RCD type, can be proposed. It will take into account the peripapillary retinal oxygen saturation, the retinal vessel diameter and the RNFL thickness values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(81 citation statements)
references
References 55 publications
12
69
0
Order By: Relevance
“…), we found once more an increased A‐SO 2 and even more, an increased V‐SO 2 , with corresponding decrease in the A‐V SO 2 values within the rod‐cone dystrophy (RCD) group (Bojinova et al. ). In the present study, we were also able to find significantly increased V‐SO 2 in the cone‐rod dystrophy (CRD) and in the inherited macular dystrophy group (IMD), and increased A‐SO 2 in the CRD group, when compared to controls.…”
Section: Materials and Methods (Described In Details: Türksever Et Almentioning
confidence: 76%
See 2 more Smart Citations
“…), we found once more an increased A‐SO 2 and even more, an increased V‐SO 2 , with corresponding decrease in the A‐V SO 2 values within the rod‐cone dystrophy (RCD) group (Bojinova et al. ). In the present study, we were also able to find significantly increased V‐SO 2 in the cone‐rod dystrophy (CRD) and in the inherited macular dystrophy group (IMD), and increased A‐SO 2 in the CRD group, when compared to controls.…”
Section: Materials and Methods (Described In Details: Türksever Et Almentioning
confidence: 76%
“…Through a significant body of knowledge, accumulated by our investigation group, the method showed its relevance for application in patients with IRDs: Our preliminary data with oximetry measurements on patients affected by inherited retinal diseases suggest the oxygen metabolism to be altered (Türksever et al 2014b;Todorova et al 2016;Bojinova et al 2017). Here, particularly in retinitis pigmentosa (RP) patients, a severe increase of venular vessel oxygen saturation, more than arteriolar vessel saturation, was found (Türksever et al 2014b;Bojinova et al 2017). The results were very promising when the venous saturation in RP was compared to the respective one in other IRDs, and even more, when compared to controls (Bojinova et al 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic signalling may play a role, as it has been shown that the peripapillary RNFL thickness in retinitis pigmentosa correlates with metabolic function and blood vessel architecture of the inner retina (Bojinova et al. ). Müller cells may contribute to inner retinal remodelling in response to photoreceptor loss in retinal degeneration (Rattner & Nathans ; Hernández et al.…”
Section: Discussionmentioning
confidence: 99%
“…gained much acceptance in studying the metabolic dysfunction in a variety of vascular and degenerative ophthalmic and generalized diseases(Eysteinsson et al 2014;Todorova et al 2014; T€ urksever et al 2014a,b;Battu et al 2015;Lopez Torres et al 2015;Ueda-Consolvo et al 2015;Einarsdottir et al 2016;Zong et al 2016;Bojinova et al 2017;Todorova 2017).…”
mentioning
confidence: 99%